Endogenous sialic acid-engineered micelles: a multifunctional platform for on-demand methotrexate delivery and bone repair of rheumatoid arthritis. Issue 6 (25th January 2018) - Xu, Xiao-Ling; Li, Wei-Shuo; Wang, Xiao-Juan; Du, Yang-Long; Kang, Xu-Qi; Hu, Jing-Bo; Li, Shu-Juan; Ying, Xiao-Ying; You, Jian; Du, Yong-Zhong
Abstract : A multifunctional carrier for methotrexate delivery and bone repair of rheumatoid arthritis. Abstract : Rheumatoid arthritis (RA) patients have suffered from the current drug therapeutic regimen because of its high toxicity and the absence of bone regeneration for existing erosion, seriously affecting the quality of life. Herein, a sialic acid-dextran-octadecanoic acid (SA-Dex-OA) conjugate was synthesized to form micelles with a 55.06 μg mL −1 critical micelle concentration. The obtained micelles can encapsulate a disease-modifying anti-rheumatic drug, methotrexate (MTX), with 4.28% (w/w) drug content, featuring sustained drug release behavior over 48 h. In vitro and in vivo studies showed that SA-Dex-OA micelles significantly improved accumulation and transportation through a combination of SA and E-selectin receptors in inflamed cells and arthritic paws highly expressing E-selectin. MTX-loaded SA-Dex-OA micelles not only significantly inhibited the inflammatory response, but also diminished the adverse effects of MTX, as reflected by the reduced alanine aminotransferase, aspartate aminotransferase, creatinine, and urea nitrogen levels. Most importantly, the bone mineral density in rats treated with MTX-loaded SA-Dex-OA micelles was significantly higher as compared to in those treated with free MTX and Dex-OA/MTX micelles (increasing from 391.4 to 417.4 to 492.7 mg cc −1 ), benefiting from the effects of endogenous sialic acid in promoting MC3T3-E1 cell differentiation and mineralization. It is anticipated that SA-based micelles with bone repair activities have great potential for RA treatment and other metabolic bone diseases with serious bone erosion.